Wakif's Behavior in Money Waqf: an Approach to Theory of Planned Behavior - Nurul Iman; Adi Santoso; Edi Kurniawan (Ekuilibrium : Jurnal Ilmiah Bidang Ilmu Ekonomi, 2021)
The Indonesian nation is a country where the development of productive waqf is very potential, but the collection of productive waqf funds, especially cash waqf, has not been optimal. This is thought to be the behavior of the muslim community that does not understand well the development of cash waqf. Based on this phenomenon, this research was conducted to find empirical evidence of the Theory of Planned Behavior and religiosity in influencing the behavior of Muslim communities to conduct cash waqf in Indonesia. This study used a quantitative descriptive approach, data collection was carried out online using the google form facility, and data collected were 138 respondents to the questionnaire that had been distributed online. The results of this study found that attitudes, subjective norms, and values of religiosity were able to influence waqf behavior in making decisions to do cash waqf.